Perlindungan Hukum Hak Kekayaan Intelektual dalam Perspektif Budaya Tradisional Papua - Pelupessy, Eddy (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research aims to analyze, explain and understand the traditional cultural expressions (folklore) of Indonesian society so that the uniqueness of traditional cultural expressions (folklore) can be discovered which is one of the foundations for finding more appropriate forms of protection and efforts to protect people's rights to traditional cultural expressions ( folklore) from misuse by other parties for commercial purposes without providing benefits to the community concerned. The type of research used is normative juridical which is carried out by examining library legal materials or secondary data, which includes research on legal principles, legal systematics, levels of vertical and horizontal synchronization, legal comparisons and legal history. The results of this research reveal that the categories of traditional cultural expressions (folklore) that can be protected are verbal and non-verbal expressions in the form of folklore, folk poetry, riddles, proverbs, proverbs, traditional speeches, song expressions, collages, traditional costumes, architects who related to folklore, has the characteristics of being sustainable, contemporary and wholeheartedly maintained, both those that have been documented and those that have not been documented at the Office of the Directorate General of Intellectual Property Rights. Therefore, the Government must be able to position itself wisely in the midst of society, namely at least by maintaining its neutrality from various social conflicts or legal disputes related to intellectual property rights or the protection of folklore in its diversity. The use of contracts to determine benefit sharing needs to be carried out by the government through institutions appointed to represent the state in the protection of folklore